Individual freedoms and agency. How can sustainable human development be reframed through citizen participation in public life? (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
Citizen action within the framework of individual freedoms represents one of the global objectives inherent to democratic systems, where the fundamental aim is to integrate individuals into the management, approach, and resolution of the requirements associated with the pursuit of their overall well-being and quality of life. This research, resulting from a qualitative documentary review, aimed to analyze the implications of individual freedoms and capacity concerning the consolidation of sustainable development, assuming the committed participation of citizens in matters related to the construction of functional, democratic, and plural contexts. The results indicate that the effective and relevant transformation of the contexts in which human beings live requires synergistic action and the willingness of individuals, as dimensions that demand the deployment of ethical and political convictions that contribute to the task of promoting actions linked to the common good, inclusive social justice, and equity. In conclusion, the exercise of individual freedoms and the capacity for agency in relation to the fundamental rights that assist every citizen inherently involve the operationalization of ideals, the conquest of spaces, and socially transformative action that makes public spaces a possibility for consolidating human development based on what is termed vital autonomy and a sense of co-responsibility.
Keywords: public affairs; citizen exercise; quality of life; overall well-being; autonomous performance